A review on wild indigenous eggplant, Terung Asam Sarawak (Solanum lasiocarpum Dunal.) - Ting, Albert Koon Soon; Ding, Phebe (Penerbit Universiti Kebangsaan Malaysia, 2021)
Terung Asam Sarawak (Solanum lasiocarpum Dunal.), also known as terung Dayak or sour eggplant is one of the largest indigenous crops in Sarawak. It has slowly gained a significant commercial importance in Malaysia especially East Malaysia. There have been several studies on Terung Asam Sarawak in the last few decades but mainly focus on plant vernacular and morphology with only some studies focusing on the fruits. The agronomic practices of the plant until fruit postharvest handling have not been comprehensively studied. The information on Terung Asam Sarawak scatters in diverse sources, either local or regional sources, and in several languages too. Therefore, this review attempts to compile these all literature and outline every important finding (from plant origin to planting, fruit postharvest handling, uses and many more) about Terung Asam Sarawak in order to pinpoint the gaps of knowledge. It is hope that this review could assist researchers to focus on the gaps that will help to establish this indigenous eggplant as an important commercial vegetable in tropical countries.